Adjusted Hospital Sentinel Lymph Node Positivity Rates in Melanoma: A Novel Potential Measure of Quality. Issue 2 (February 2016) - Kinnier, Christine V.; Paruch, Jennifer L.; Dahlke, Allison R.; Wayne, Jeffrey D.; Benson, Al B.; Winchester, David P.; Bilimoria, Karl Y.
Abstract : Objective: Our objectives were to examine whether hospital characteristics are associated with lower- and higher-than-expected sentinel lymph node biopsy (SLNB) positivity rates and whether hospitals with lower- or higher-than-expected SLNB positivity rates have worse patient outcomes. Background: Surgeon and pathologist SLNB technical errors may lead to incorrect melanoma staging. A hospital's SLNB positivity rate may reflect its SLNB proficiency for melanoma, but this has never been investigated. Methods: Stage IA-III melanoma patients undergoing SLNB were identified from the National Cancer Data Base (2004–2010). Hospital-level SLNB positivity rates were adjusted for patient- and tumor factors. Hospitals were divided into terciles of adjusted SLNB positivity rates. Hospital characteristics (using multinomial logistic regression) and survival (using Cox modeling) were examined across terciles. Results: Of 33, 639 SLNB patients (from 646 hospitals), 2916 (8.7%) had at least 1 positive lymph node. Hospitals with lower- (low tercile) and higher-than-expected (high tercile) SLNB positivity rates were more likely to be low-volume hospitals (low tercile: relative risk ratio (RRR) = 2.57, P = 0.002; high tercile: RRR = 2.3, P = 0.004) compared to hospitals with expected rates (middle tercile). Stage I patients treated at lower-than-expected SLNB positivity rate hospitals had worse 5-year survival than those treated at expected SLNB positivity rate hospitals (90.0% vs 91.9%, P = 0.014; hazard ratio = 1.28, 95% CI: 1.05–1.57); survival differences were not observed by SLNB positivity rates for stage II/III. Conclusions: Adjusted hospital SLNB positivity rates varied widely. Surgery at hospitals with lower-than-expected SLNB positivity rates was associated with decreased survival. Hospital SLNB positivity rates may be a novel measure to confidentially report to hospitals for internal quality assessment.